The significance of Rumah Terbuka during Eid festivity in promoting visitor attraction / Rosmaliza Muhammad … [et al.] - Muhammad, Rosmaliza; Mohamad Abdullah, Khairunnisa; Ismail, Faridah Hanim; Abdullah, Nurhidayah; Abdul Ghani, Arni (Penerbit UiTM (Press), 2018)
Owing to the multi-ethnic backgrounds, Malaysians celebrate their annual festivals and all of the celebrations have become a cultural tradition. The major ethnic group festival celebrations include Hari Raya Aidilfitri (Malays), Deepavali (Indians) and Chinese New Year (Chinese), have been recognised by the Malaysian government to be a national celebration and yearly events. These events are popularly known as Rumah Terbuka. Even though the celebration of Rumah Terbuka festivals have started and celebrated widely many years ago, each celebration has managed to attract a huge crowd from different ethnicities and backgrounds. People are willing to spend time queuing which sometimes could stretch into long hours before they can be seated and enjoy the Rumah Terbuka festivals. Therefore, it raises a question on factors that influence visitors to attend the festivals. Hence, this study empirically examines the factors that influence visitors to attend the Rumah Terbuka Aidilfitri festival. Using this festival in Perak as the contextual setting, the visitors were given questionnaires to be answered. Through a series of analyses, some useful insights or predictors on the issue of interest were obtained. Majority of the respondents demonstrated positive responses on the attributes of the festival. Improvement needs to be done by the government authorities or the organiser in planning and managing such festival in order to increase visitor satisfaction. The findings for this study could contribute to the body of new knowledge regarding the festival celebration.